Reconstruction of teeth with intraradicular retainers: a literature review (Research, Society and Development, 2020)
Objective: To conduct a literature review on prefabricated fiberglass intra root pins. Methodology: A search was performed in the PubMed and Google Scholar databases with the following descriptors: “Post and Core Technique”, “Treatment” and “Dental Restoration Failure”. Results: Among the advantages of prefabricated intra root pins systems, one can highlight the low cost, simplicity of the technique, conservation of the remaining dental structure, elimination of the laboratory phase, and yet, the carbon fiber and glass pins have similar elasticity module that of dentin and similar flexion to that of the tooth, which reduces the risk of fractures when compared to molten metal cores. In addition, fiberglass pins have the advantage of being more translucent, which allows for a greater transmission of light, making them more aesthetic. Conclusion: Fiberglass pins are currently considered the best option for the rehabilitation of teeth treated endodontically with extensive coronary loss, since they have an elasticity module similar to that of dentin, flexion resistance, simplicity of the technique, less clinical time and have superior aesthetics to other intra root pins.